'Try to make good hay in the shade – it won't work!' A qualitative interview study on the perspectives of Bavarian farmers regarding primary prevention of skin cancer. (19th April 2019) - Zink, A.; Schielein, M.; Wildner, M.; Rehfuess, E.A.
Summary: Background: Extensive exposure to solar ultraviolet radiation (UVR) is the main risk factor for keratinocyte carcinoma (KC), making outdoor workers, including farmers, a high‐risk population for KC. The use of sun protection is crucial for KC prevention but is not typically implemented by outdoor workers during their daily tasks. Objectives: To explore the attitudes of Bavarian farmers regarding sun‐protective measures in their daily work and to understand perceived barriers and unmet needs. Methods: Farmers were recruited through the Bavarian Farmers Association in Bavaria, Southern Germany. Qualitative semi structured interviews were conducted with participants between December 2017 and March 2018. Interviews were recorded, transcribed verbatim and analysed using qualitative content analysis. Results: Twenty farmers (11 women, nine men; nine aged 18–30 years, 11 aged > 60 years) participated. Knowledge and awareness of UVR exposure and KC, perceived individual barriers to implementing sun‐protective measures, individual experiences and farm life‐specific circumstances emerged as key areas influencing the perspectives of farmers regarding the primary prevention of KC. Female farmers tended to take a more positive stance on sun protection, whereas male farmers showed a lower overall interest. Conclusions: Knowledge and awareness of KC and UVR exposure is very limited in Bavarian farmers with serious perceived barriers due to the demands of daily agricultural work. Further qualitative studies are needed to identify intervention options that can increase skin cancer awareness and that can successfully overcome real barriers to implementing sun protection. Abstract : What's already known about this topic? Outdoor workers, including farmers, have a substantially increased risk of keratinocyte carcinoma (KC) induced by solar ultraviolet radiation (UVR). Farmers in Bavaria and elsewhere typically show poor sun‐protective behaviour, but little is known about the underlying reasons. What does this study add? This qualitative interview study provides insights into farmers' perspectives on the primary prevention of KC and identifies important determinants of sun‐protection behaviour. Lack of knowledge about KC and UVR exposure as a major risk factor, as well as barriers associated with the demands of daily agricultural work, are highlighted as factors that limit sun‐protective behaviour. What are the clinical implications of the work? Strategies to increase self‐efficacy beyond basic efforts to raise awareness of KC and UVR could be the key to preventing KC in farmers. Further qualitative studies are needed to explore different intervention options that can successfully overcome barriers to implementing sun protection. Linked Editorial: Nelson et al. Br J Dermatol 2019; 180 :1271–1273 . Linked Comment: Apfelbacher. Br J Dermatol 2019; 180 :1291–1292 . Respond to this article